PERAN MAJELIS PENGAWAS DAERAH KABUPATEN KARIMUN DALAM MENYELENGGARAKAN FUNGSI PENGAWASAN, PEMERIKSAAN DAN PENJATUHAN SANKSI TERHADAP NOTARIS - Indrawan; Azmi; Edi kurniawan (PROGRAM STUDI ILMU KOMUNIKASI, 2022)
The purpose of the study was to determine the implementation of the supervisory duties of notary positions by the Regional Notary Supervisory Council of Karimun Regency which refers to Article 1 paragraph 5 of the Ministerial Regulation number M.02.PR.08.01 of 2004 that supervision is a preventive and curative activity. Preventive activities include administrative authorities, while curative activities are activities regarding taking action against alleged violations committed by a notary against UUJN and the code of ethics. Obstacles and solutions to the implementation of the task of supervising the position of a notary by the Regional Supervisory Council of Sleman Regency has not done much outreach to related parties, including community elements, academic elements, the Indonesian police, there is no training for notary members in terms of conducting inspections, standards assessments that have not explained in detail, the lack of implementing regulations for UUJN in relation to the guidance and supervision carried out by the Notary Supervisory Council, the absence of a clear vision regarding the performance of the MPD, apart from carrying out routines once a year, and the absence of coordination between the MPD, MPW, MPP As for the Notary who violates the Code of Ethics, the Honorary Council in coordination with the Supervisory Council is authorized to conduct an examination of the violation and may impose sanctions on the violator and several differences related to technical inspections related to the notary document, so that the epan needs to gradually and carry out a work evaluation once a year regarding MPD performance